Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.12688/f1000research.21397.1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Helicobacter pylori infection and intestinal parasites in individuals from Khartoum state, Sudan: a case-control study

Abstract: In developing countries, infection is Background:Helicobacter pylori common, as are intestinal parasites. Socioeconomic circumstances and low personal hygiene lead to the spread of these infections. This research aimed to evaluate the relationship between intestinal parasites and H. pylori in Khartoum, Sudan.This study was conducted in various hospitals in Khartoum Methods: between June and October 2018. The study involved 200 individuals: 100 patients with as a case group and 100 healthy individuals as a H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Abd Elbagi et al (2019) in Sudan reported that among 100 H. pylori patients that 23% had H. pylori and 10% of healthy individuals had gastrointestinal parasites; Entamoeba histolytica was detected in 12% of H. pylori cases followed by Entamoeba coli (7%) and Giardia lamblia (4%). The control ones (100), E. histolytica was detected in 5% followed by G. lamblia in 3% and E. coli in 2% of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Abd Elbagi et al (2019) in Sudan reported that among 100 H. pylori patients that 23% had H. pylori and 10% of healthy individuals had gastrointestinal parasites; Entamoeba histolytica was detected in 12% of H. pylori cases followed by Entamoeba coli (7%) and Giardia lamblia (4%). The control ones (100), E. histolytica was detected in 5% followed by G. lamblia in 3% and E. coli in 2% of individuals.…”
Section: Introductionmentioning
confidence: 99%